Childhood Mycosis Fungoides: Experience of 28 Patients and Response to Phototherapy. Issue 4 (11th June 2014) - Laws, Philip M.; Shear, Neil H.; Pope, Elena
Abstract Mycosis fungoides (MF), the most common cutaneous T‐cell lymphoma (CTCL), is rare in childhood. The prognosis and response to treatment are poorly described in children. The objective of the current study was to evaluate the response to phototherapy in a pediatric cohort. A retrospective cohort study of all patients diagnosed with MF before the age of 18 years and referred to the regional CTCL phototherapy service was performed between January 1990 and April 2012. Twenty‐eight patients were identified (13 boys, 15 girls). The mean age at presentation was 11.6 ± 3.9 years. The hypopigmented variant was noted in 79% of patients. All patients had stage I disease (IA = 10, IB = 17, unknown = 1). The median follow‐up after diagnosis was 43 months (range 6–274 mos). Narrowband ultraviolet B (NbUVB; 311 nm) was used as first‐line phototherapy in 18 patients and psoralen (bath) plus ultraviolet A (PUVA) was used in 8 patients. Complete or partial response was observed in 19 of 22 patients (86%). A further course of phototherapy was required in 7 of 12 patients (58%) treated with NbUVB after a median of 4 months (range 4–29 mos). A further course of phototherapy was required in four of eight patients (50%) successfully treated with PUVA after a median of 45.5 months (range 30–87 mos). No disease progression was noted over the follow‐up (median 43 mos). The majority of patients in our cohort had hypopigmented MF. Phototherapy offers an effective option for treatment of childhood MF, although the period of remission may be greater in patients treated with PUVA.